2007
DOI: 10.1203/pdr.0b013e31805365ef
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric HIV-1–Specific Cytotoxic T-Lymphocyte Responses Suggesting Ongoing Viral Replication Despite Combination Antiretroviral Therapy

Abstract: Human immunodeficiency virus-1 (HIV-1)-specific cytotoxic T-lymphocyte (CTL) responses are common in infected adults and usually exhibit rapid decay after combination antiretroviral therapy (ART). CTLs develop later in the first year of life, and the fate of HIV-1-specific responses in perinatally infected children after ART is less well described. HIV-1-specific CTL responses were measured in 17 perinatally infected children and adolescents (ages 3-20 y) receiving combination ART. Seven had prolonged viral su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Many studies of HIV-1-specific T-cell immunity have used pools containing from 2 to over 100 HIV-1 synthetic peptides of 8 to 20 aa in length (3,7,9,14,17,24,25,31,32,34,37,49). These peptides have been added directly to the PBMC or purified T cells to gauge peptide-specific immune responses in persons with HIV-1 infection or in anti-HIV-1 drug treatment and vaccine trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies of HIV-1-specific T-cell immunity have used pools containing from 2 to over 100 HIV-1 synthetic peptides of 8 to 20 aa in length (3,7,9,14,17,24,25,31,32,34,37,49). These peptides have been added directly to the PBMC or purified T cells to gauge peptide-specific immune responses in persons with HIV-1 infection or in anti-HIV-1 drug treatment and vaccine trials.…”
Section: Discussionmentioning
confidence: 99%
“…There is little information, however, as to whether these professional APC can similarly enhance other T-cell functions that could be critical to control of HIV-1 infection, particularly their proliferative capacity and ability to produce multiple immune mediators. Moreover, many current approaches for measuring the magnitude and breadth of T-cell responses use pools of various numbers of synthetic peptides, usually 15 or 20 amino acids (aa) in length, which overlap by 10 to 11 aa (1,3,7,9,13,14,17,24,25,27,32,37,45,48,49), developed by Kern et al (26) and Maecker et al (31). Such studies have not accounted for a role of APC in processing that is required to reduce these peptides to their optimal, 8-to 10-mer length for presentation by MHC class I molecules to CD8 ϩ T cells (43), or to 13-to 17-mers for presentation by MHC class II to CD4 ϩ T cells (46).…”
mentioning
confidence: 99%
“…We note that the persistence of broad antiviral responses to HIV during cART has previously been observed in other perinatally-infected persons and contrasts with the situation in older adults, in whom complete decay of these responses is common. [37, 42-45]…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that residual viral replication continues in patients under potent combination therapy even when the viral loads have been suppressed to below the limit of detection for a long time [17, 28, 29, 62, 115, 168]. This low-level ongoing virus replication involves generation of new infected cells through de novo infection from the virus released from other infected cells.…”
Section: Low-level Viremic Persistencementioning
confidence: 99%